2020
DOI: 10.1155/2020/8492097
|View full text |Cite
|
Sign up to set email alerts
|

A New Therapy for Vitiligo Using Fire Needles: A Systematic Review of Evidence from 3618 Subjects

Abstract: Introduction. Fire needle therapy has been reported as an effective treatment for vitiligo. However, current clinical evidence has not been systematically evaluated. The aim of this study was to determine whether fire needle therapy is effective and safe for treating vitiligo. Methods. Seven databases were searched until October 2019 for randomized controlled trials on fire needle therapy, with and without conventional treatments, versus any type of conventional therapy for treating vitiligo. The RevMan 5.3.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…Metafor (R package) was utilized for meta-analysis of identical trials and control methods. The calculation of the mean difference and the confidence interval up to 100% was used to evaluate the data measurement and the total effective rate, which was regarded as the relative risk with a confidence interval in the 95% range [ 20 ]. The statistical analysis of the same statistics was represented by the corresponding I value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metafor (R package) was utilized for meta-analysis of identical trials and control methods. The calculation of the mean difference and the confidence interval up to 100% was used to evaluate the data measurement and the total effective rate, which was regarded as the relative risk with a confidence interval in the 95% range [ 20 ]. The statistical analysis of the same statistics was represented by the corresponding I value.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent clinical trials have demonstrated that fire needle therapy is an effective psoriasis treatment; however, there are few comprehensive reviews of the therapy's efficacy [ 19 ]. Combined with other methods, the fire needles used to treat vitiligo are more efficacious [ 20 ]; vitiligo is a skin-lightening disease caused by hereditary melanocyte depletion and decreased melanin biosynthesis [ 21 ]. A fine needle is also utilized during acupuncture treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Fire needle has the advantages of both conventional acupuncture and moxibustion, due to needle and thermal stimulation. It can promote microcirculation, accelerate metabolism, and restore damaged tissues in the lesional area through the regulation of cutaneous nerves, which in turn can eliminate or attenuate pathological features such as edema, hyperemia, exudation, adhesion, calcification, contractures, and ischemia[ 5 ]. Fire needle also can stimulate vascular dilatation and local edema of the lesion, which promotes transdermal absorption and maximizes the efficacy of the topical agents[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acupuncture needle pierces the lesion quickly after being burned red on an alcohol lamp. It has been reported that fire needle can be used for treatment of itchy, painful, inflammatory, and pigmented diseases[ 1 - 5 ], and has achieved a good therapeutic effect as an adjuvant therapy. Here, we report two cases of PCA that received fire needle pre-treatment and topical halometasone cream (Bright Future Pharmaceuticals Factory, Hong Kong), who achieved significant improvement.…”
Section: Introductionmentioning
confidence: 99%
“…It could stimulate and dredge the meridians and accelerate the flow of Qi and blood thus dissipating nodules. On this basis, the fire needles therapy has been proven to treat nodular prurigo [ 17 ], moderate severe acne [ 18 ], vitiligo [ 19 ]and psoriasis [ 20 , 21 ]. Recently, fire needle therapy has also been used to treat flat warts, and its possible therapeutic mechanism may be destroying the wart body, improving local circulation, and promoting the local immune response.…”
Section: Introductionmentioning
confidence: 99%